Analysis of risk factors for the recurrence of osteomyelitis of the limb after treatment with antibiotic-loaded calcium sulfate and autologous bone graft - Su, Yu; Li, Dongchen; Du, Bing; Li, Zhao; Lu, Yao; Xu, Yibo; Wang, Qian; Li, Zhong; Ren, Cheng; Ma, Teng (Frontiers in Bioengineering and Biotechnology, 2024)
We aimed to evaluate the efficacy of antibiotic-loaded calcium sulfate combined with autologous iliac bone transplantation in the treatment of limb-localized osteomyelitis (Cierny-Mader type III) and analyze the causes and risk factors associated with infection recurrence.Methods: Clinical data of 163 patients with localized osteomyelitis of the extremities treated with antibiotic-loaded calcium sulfate combined with autologous iliac bone transplantation in Xi'an Honghui Hospital from January 2017 to December 2022 were retrospectively analyzed. All patients were diagnosed with localized osteomyelitis through clinical examination and treated with antibioticloaded calcium sulfate combined with autologous iliac bone. Based on the infection recurrence status, the patients were divided into the recurrence group and the non-recurrence group. The clinical data of the two groups were compared using univariate analysis. Subsequently, the distinct datasets were included in the binary logistic regression analysis to determine the risk and protective factors.Results: This study included 163 eligible patients, with an average age of 51.0 years (standard deviation: 14.9). After 12 months of follow-up, 25 patients (15.3%) experienced infection recurrence and were included in the recurrence group; the remaining 138 patients were included in the nonrecurrence group. Among the 25 patients with recurrent infection, 20 required reoperation, 4 received antibiotic treatment alone, and 1 refused further treatment. Univariate analysis showed that education level, smoking, hypoproteinemia, open injury-related infection, and combined flap surgery were associated with infection recurrence (P<0.05). Logistic regression analysis showed that open injuryrelated infection (odds ratio [OR]=35.698; 95% confidence interval [CI]:5.997-212.495;P<0.001) and combined flap surgery (OR=41.408;95%CI:5.806-295.343;P<0.001) were independent risk factors for infection recurrence. Meanwhile, high education level (OR=0.009;95%CI:0.001-0.061; P<0.001) was a protective factor for infection recurrence.Antibiotic-loaded calcium sulfate combined with autologous iliac bone transplantation is an effective method for treating limb-localized osteomyelitis. Patients without previous combined flap surgery and non-open injury-related infections have a relatively low probability of recurrence of infection after treatment with this surgical method. Additionally, patients with a history of smoking and hypoproteinemia should pay attention to preventing the recurrence of infection after operation.Providing additional guidance and support, particularly in patients with lower education levels and compliance, could contribute to the reduction of infection recurrence.